Use of computerized tomography for diagnosis and follow-up after endodontic surgery: clinical case report with 8 years of follow-up - Tanomaru-Filho, Mario [UNESP]; Lima, Regina K. P. [UNESP]; Nakazone, Paula A. [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP] (Mosby-elsevier, 2010)
Computerized tomography (CT) is a valuable tool for diagnosis and planning in conventional and surgical endodontic therapy. This case report describes the use of CT in the diagnosis of a periapical lesion undetected by periapical radiography in the mandibular molar area. The CT also showed a possible mesial root perforation associated with the lesion. Following CT, surgical planning, periradicular curettage, and sealing of the root perforation were performed. Eight years after surgery, cone beam CT revealed periapical bone repair. Computerized tomography can be an important resource for diagnosis and planning in conventional and surgical endodontic therapy, as well as for evaluation of post-treatment bone repair. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2010; 109: 629-633)